'Red Ellen' Wilkinson : Her ideas, movements and world - Perry, Matt, 1967- (Book collections on Project MUSE., 2014)
This study seeks to delve beyond the familiar image of Ellen Wilkinson as the leader of the Jarrow Crusade. It has attempted to unearth new evidence to provide a richer understanding of this figure who is remarkable in terms of her achievements, her acquaintances and her witnessing of history's great turning points. From a humble background, she ascended to the rank of Minister in the 1945 Labour government. Yet she was much more than a conventional Labour politician. She wrote journalism, political theory and novels. She was both a socialist and a feminist; at times, she described herself as a revolutionary.